Factors influencing management of bilateral femur fractures: A multicenter retrospective cohort of early versus delayed definitive Fixation. Issue 8 (August 2021) - Flagstad, Ilexa R.; Tatman, Lauren M.; Albersheim, Melissa; Heare, Austin; Parikh, Harsh R.; Vang, Sandy; Westberg, Jerald R.; de Chaffin, Danielle Ries; Schmidt, Tegan; Breslin, Mary; Simske, Natasha; Siy, Alexander B.; et al.
Highlights: High-volume institutions were found to be the primary driver of variability in management of bilateral femur fractures. There is considerable variation amongst institutions in timing of definitive surgery for bilateral femur fractures. ISS is a direct influencer in timing of definitive surgery for bilateral femur fractures. Abstract: Introduction: The purpose of our study was to evaluate the factors that influence the timing of definitive fixation in the management of bilateral femoral shaft fractures and the outcomes for patients with these injuries. Methods: Patients with bilateral femur fractures treated between 1998 to 2019 at ten level-1 trauma centers were retrospectively reviewed. Patients were grouped into early or delayed fixation, which was defined as definitive fixation of both femurs within or greater than 24 hours from injury, respectively. Statistical analysis included reversed logistic odds regression to predict which variable(s) was most likely to determine timing to definitive fixation. The outcomes included age, sex, high-volume institution, ISS, GCS, admission lactate, and admission base deficit. Results: Three hundred twenty-eight patients were included; 164 patients were included in the early fixation group and 164 patients in the delayed fixation group. Patients managed with delayed fixation had a higher Injury Severity Score (26.8 vs 22.4; p<0.01), higher admission lactate (4.4 and 3.0; p<0.01), and a lower Glasgow Coma Scale (10.7 vs 13; p<0.01). High-volume institution was the most reliable influencer for time to definitive fixation, successfully determining 78.6% of patients, followed by admission lactate, 64.4%. When all variables were evaluated in conjunction, high-volume institution remained the strongest contributor (X 2 statistic: institution: 45.6, ISS: 8.83, lactate: 6.77, GCS: 0.94). Conclusion: In this study, high-volume institution was the strongest predictor of timing to definitive fixation in patients with bilateral femur fractures. This study demonstrates an opportunity to create a standardized care pathway for patients with these injuries. Level of Evidence: Level III